PENGARUH PENDIDIKAN KESEHATAN DENGAN VIDEO PEMBELAJARAN TENTANG CARA MENGGOSOK GIGI YANG BENAR PADA ANAK USIA SEKOLAH - Nurdin, Ambia; Zamzami, Zamzami; Muhammad, Muhammad; Murtadhahadi, Murtadhahadi; Bukhari, Bukhari; Fitria, Ricky Dear; Mahyuddin, Mahyuddin; Fuadi, Zahrul; Mulyadi, Mulyadi; Astini, Dewi; Megawati, Cut; Bahri, Idal; Pangastuti, Yunida (Jurnal Dedikasi Pendidikan, 2024)
Health is an aspect that is very significant in supporting the processes of human life, such as oral and dental health. School-age children are a time when children gain basic knowledge about the importance of cleanliness, especially oral hygiene. School-age children experience many dental and oral health problems such as caries and cavities at this time. The results of basic health research (Riskesdas) in 2018 proved that the prevalence of dental caries in the Indonesian population, including children, was around 80%, while in Aceh people who experienced dental caries reached 80%. Health education is needed as an effort to improve skills, awareness, attitudes and actions. School age children need appropriate learning methods to improve their knowledge and skills in brushing their teeth, one of which is simulation and audiovisual methods such as video media. The purpose of this study was to determine the effect of health education with video lessons on the correct way to brush teeth in school age children. This study is a study using the literature study method by examining 14 journals (9 national journals and 5 international journals) related to the knowledge of brushing teeth in school-age children from all objects studied and considered to be representative of the entire population. The sampling technique in this research was literature review, namely elementary school students. The results of the study were 9 journals that were relevant, using video media, that health education with instructional videos had an effect on students' abilities on how to brush their teeth properly. While 5 journals do not use video media, they are still related to the title of the researcher. Based on the results of the study, the researchers suggest that this research can be used as a reference in providing health education on how to properly brush teeth for school-age children, especially through video media.